2010
DOI: 10.1007/s10753-009-9176-5
|View full text |Cite
|
Sign up to set email alerts
|

Different Mechanisms in Formation and Prevention of Indomethacin-induced Gastric Ulcers

Abstract: Indomethacin is an indol derivative, non-steroidal, anti-inflammatory drug with anti-inflammatory, analgesic, and antipyretic effects. Indomethacin became the first-choice drug to produce an experimental ulcer model as a result of having a higher ulcerogenic potential than other non-steroidal anti-inflammatory drugs (NSAIDs). There have been several conflicting reports about the ulcerogenic mechanism of indomethacin; the mechanism is still unclear. It has been suggested that indomethacin induces gastric damage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
150
1
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(179 citation statements)
references
References 102 publications
10
150
1
7
Order By: Relevance
“…Although its mechanism of action is not completely understood, it is believed that indomethacin induces gastric damage, mainly due to its systemic effect, inhibiting COX-1 and COX-2 and reducing the local concentration of prostaglandins (PGs), which are involved in mucus and bicarbonate production (10,23) .…”
Section: Discussionmentioning
confidence: 99%
“…Although its mechanism of action is not completely understood, it is believed that indomethacin induces gastric damage, mainly due to its systemic effect, inhibiting COX-1 and COX-2 and reducing the local concentration of prostaglandins (PGs), which are involved in mucus and bicarbonate production (10,23) .…”
Section: Discussionmentioning
confidence: 99%
“…4,19,20 In general speaking, stress induces gastric mucosal lesions by complex psychological factors including a decrease in the release of protective factors like PGE2, antioxidant enzymes, bicarbonate, and mucus with an increase in the aggressive factors like acid. 21 Stress leads to activation of hypothalamic pituitary adrenal cortex axis, decrease blood flow to the mucosa by vasoconstriction, stomach mast cell degranulation with histamine production, change in gastric motility and emptying rate and increases free radical generation resulting in increased lipid peroxidation. 22,23 Both clinical and preclinical studies have shown that psychological stress enhances helicobacter pylori infection and colonization of the stomach and this is facilitated in part through glucocorticoids.…”
Section: Discussionmentioning
confidence: 99%
“…Наряду с терапевтическим эффектом, уменьшение синтеза простациклина PGI и простагландина PGE2 приводит к снижению секреции желудочной слизи, снижению pH желудочного сока, усилению моторики желудка, развитию апоптоза эпителиоцитов и, в конечном итоге, к формированию пептической язвы (ульцерогенному эффекту) [2]. Условием развития язв является ингибирование обеих форм циклооксигеназы (ЦОГ-1 и ЦОГ-2), что приводит к более существенному снижению синтеза простагландинов, чем при их ингибировании по отдельности [3]. Тот факт, что ЦОГ-1 является конститутивным ферментом, а ЦОГ-2 в большей степени экспрессируется при воспалении, послужил основой для разработок селективных ингибиторов ЦОГ-2, которые реже приводят к развитию язв.…”
unclassified
“…Морфин, который снижает секрецию соляной кислоты в желудке, предотвращает развитие аспириновых язв, но не обладает гастропротективным эффектом в случае применения индометацина и даже усиливает его ульцерогенное действие [3]. Кетотифен, стабилизатор мембран тучных клеток, обладает противоязвенным эффектом, снижая при этом синтез простагландинов [3].…”
unclassified
See 1 more Smart Citation